Chemical control of white grub Liogenys fuscus (Blanchard 1851) (Coleoptera: Melolonthidae) in cornfields - Santos, Antônio; Bueno, Adeney; Bueno, Regiane; Vieira, Simone (BioAssay, 2009)
Soil pests such as the white grub complex are of great importance in different Brazilian regions, and Liogenys fuscus (Blanchard) is the most common species at the Brazilian Western Central Region. Corn producers had largely relied on pesticides to keep initial pest outbreaks under control, however, there is little information regarding the efficacy of different insecticides to control L. fuscus. The objective of this research was to evaluate the effectiveness of some insecticides, applied either to the soil or the seed, in controlling L. fuscus in cornfields in State of Goiás during two crop seasons. In 2004/2005 season the following chemicals were applied in furrow: chlorpyrifos (450, 675, 900, and 1170 g.ha-1); endosulfan (525 g.ha-1); and fipronil (160 g.ha-1). During the 2005/2006 season the treatments were chlorpyrifos (450 and 675 g.ha-1), fipronil (160 g.ha-1), both applied in furrow, as well as fipronil (37.5 and 50 g.100 kg of seeds-1) and thiamethoxan (70 g.100 kg of seeds-1) applied as seed treatment. The results showed that chlorpyrifos (450.0 g.ha-1) in furrow was effective to control L. fuscus. Plant stand and plant size in this treatment were 7-fold and 2-fold taller than plants in the control plots, during the 2004/2005 season. Similarly, fipronil 160.0 g.ha-1 applied in furrow had positive results, both outperforming endosulfan 525.0 g.ha-1 in furrow application. However, during the 2005/2006 season there was no benefit regarding plant stand or plant size due to insecticide application, and no pest injury was observed in the plants. During this crop season, results recorded for the seed treatment (fipronil 37.5 and 50 g.100 kg of seeds-1 and thiamethoxan 70 g.100 kg of seeds-1) were also similar to the chlorpyrifos and fipronil in furrow treatment, which may be considered to be used as a chemical control procedure. Therefore, under conditions similar to those prevalent during the execution of these trials, in furrow application of chlorpyrifos and fipronil as well as seed treatment with fipronil and thiamethoxan may be used to control L. fuscus outbreaks in cornfields.